Exploring acculturative stress and coping mechanisms among pregnant South Asian immigrants in Ontario, Canada: A qualitative study protocol - Anam Shahil-Feroz; Mehtab Jaffer; Kateryna Metersky; Saleema Allana; Salima Meherali; Shokoufeh Modanloo; Usha George; Samya Hasan; Zohra Lassi (PLoS ONE, 2026)
Background Canada’s South Asian immigrant population has grown by 154% over the past two decades, making it the largest visible minority group in the country. Many Pregnant South Asian Immigrants (PSAIs) have unique reproductive well-being needs and face challenges adapting to new cultural and social contexts. Despite support from agencies like the Council of Agencies Serving South Asians (CASSA), PSAIs encounter cultural differences, language barriers, limited social support, financial uncertainties, and restricted access to culturally responsive resources. These factors increase acculturative stress, yet there is limited evidence on how PSAIs experience and cope with these stressors. Goal and objectives This one-year project aims to deepen understanding of acculturation challenges faced by PSAIs in Ontario through two objectives: (1) explore PSAIs’ experiences of acculturative stress and coping mechanisms, focusing on cultural, social, and structural factors that increase stress during pregnancy, and (2) develop actionable recommendations to inform strategic adaptations of existing programs and services to better meet PSAIs’ needs. Methods and analysis A constructivist qualitative design will be used to conduct 25-30 semi-structured interviews with PSAIs in Ontario. Interviews will explore perceptions related to cultural adaptation, language barriers, social support, sources of stress, and coping mechanisms. Data will be analyzed using Braun and Clarke’s reflexive thematic analysis and guided by Berry’s acculturation framework. The analysis will identify key themes on acculturation, stress, and coping. Data will inform evidence-based recommendations to improve support programs and services. Ethics Ethical approval has been obtained from Western University Health Sciences Research Ethics Board (HSREB) in June 2025 (Protocol # 127113). Discussion This project will enhance understanding of PSAIs’ acculturation experiences in Ontario, identify gaps in current supports, explore coping mechanisms, and assess needs. Findings will inform culturally safe interventions and resources and lay the foundation for future interdisciplinary studies focused on co-designing, implementing, and evaluating culturally relevant supports for PSAIs.